High-strength double-network gel for sealing channeling of pressure-driven well cracks and preparation method thereof

By using a dual-network gel formed by the synergistic combination of low-molecular-weight and medium-molecular-weight polymers, the problem of easy shear failure of gel under high pressure and high speed conditions has been solved, achieving high-strength plugging and temperature and salt resistance, and improving the water injection efficiency of pressure-driven wells.

CN120904867APending Publication Date: 2025-11-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410551610.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing high molecular weight polymer gels are prone to shear failure under high pressure and high speed conditions, leading to water leakage in pressure-driven wells, insufficient sealing strength, and inability to effectively expand the affected area and improve displacement efficiency.

Method used

By employing the synergistic effect of low and medium molecular weight polymers, a dual-network gel is formed. Crosslinking with phenolic and aldehyde crosslinking agents improves the gel's shear resistance, temperature resistance, and salt resistance, thereby enhancing its sealing strength.

Benefits of technology

It forms a high-strength gel slug in the fracture of the pressure-driven well, effectively plugging water, expanding the water injection sweep area, improving the sweep efficiency, with a plugging rate of over 95%, and is resistant to temperatures of 130℃ and salt concentrations of 100,000 mg/L.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-strength double-network gel for sealing cracks of a pressure-driven well, which comprises the following components in parts by mass: 0.5-2 parts of low-molecular-weight emulsion polymer; 0.1-0.3 part of a medium molecular weight polymer; 0.1 to 0.4 part of a phenol cross-linking agent; 0.1 to 0.4 part of an aldehyde cross-linking agent; 0.3 part of a deoxidant; the high-strength double-network gel is suitable for the technical field of oilfield chemistry, the high-strength double-network gel is constructed through the synergistic effect of a low-molecular-weight polymer and a medium-high-molecular-weight polymer, the shear resistance and the plugging strength are improved, and the high-strength double-network gel has the advantages that the high-strength double-network gel is suitable for plugging the fracture of the pressure-driven well; the shear resistance, the temperature resistance, the salt tolerance and the strength of the gel are greatly improved, a high-strength gel slug can be formed in a pressure-driven crack, then water is effectively plugged, the pressure-driven water injection swept area is enlarged, and the swept efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of oil field chemistry, and specifically relates to a high-strength double-network gel for sealing channeling of fractures of pressure displacement wells and a preparation method thereof. BACKGROUND

[0002] Pressure displacement water injection is a new low-permeability reservoir development method in recent years, which can effectively improve the current situation of low energy and low liquid in low-permeability reservoir development. The pressure displacement development technology combines hydraulic fracturing equipment with water injection development, and realizes rapid replenishment of reservoir energy and improvement of reservoir pressure in a short time through high pressure (the wellhead injection pressure is generally greater than 35 MPa) and high speed (the single well daily water injection volume is generally greater than 1000 m 3 / d), thereby improving the production pressure difference, liquid production volume and oil production volume of the oil well, and is an important technical means for improving the recovery rate of low-permeability reservoirs. However, the high-pressure and high-speed water injection process is easy to cause the communication between natural fractures and reconstructed fractures in the reservoir, and also easy to induce complex dynamic fractures. This leads to the easy channeling of injected water in the pressure displacement well, which affects the swept area and displacement efficiency, and effective water shutoff and channeling sealing measures are urgently needed.

[0003] Polymer gel is one of the most commonly used plugging agents for sealing channeling in oil fields. Chinese patent CN 112724947 A discloses a high-temperature-resistant and high-strength gel material and its application. The gel material comprises partially hydrolyzed polyacrylamide, an organic crosslinking agent and water, and has excellent high-temperature resistance and pressure resistance.

[0004] Chinese patent CN 106479463 A discloses a slow-crosslinking high-strength gel profile control and water plugging agent, which is composed of hydrophobic associated polymer, melamine resin crosslinking agent, phenolic crosslinking agent, oxygen scavenger, delayed crosslinking agent, dehydration inhibitor and water. The strength can reach H level or above, and there is no dehydration after 270 days of treatment at 60-90 DEG C.

[0005] Chinese patent CN 113025292 A provides a high-strength gel temporary plugging agent for sealing horizontal wellbore before workover of thermal recovery horizontal well and a preparation method thereof. The plugging agent is composed of temperature-resistant polymer, partially hydrolyzed polyacrylamide, phenolic crosslinking agent, chromium crosslinking agent, oxygen scavenger, organic acid, sodium soil and the rest of water. The plugging agent can quickly crosslink to form a high-strength gel plug at a temperature higher than 100 DEG C, and can temporarily plug for 3-5 days at 200 DEG C.

[0006] It can be seen that the above-mentioned gel plugging agent is usually composed of high molecular weight polymer and crosslinking agent, and can form a certain strength sealing in the reservoir. However, the sealing channeling of pressure displacement water injection development well group puts forward higher requirements for the performance of the plugging agent. The high pressure condition requires the plugging agent to have higher sealing strength, and the high-speed water injection requires the plugging agent to have better shear resistance and scour resistance. The existing high molecular weight polymer has a long main chain, which is easy to be severely sheared under high pressure and high speed conditions, and the sealing channeling strength of the formed gel is insufficient.

[0007] Therefore, it is urgent to develop a new gel channeling sealing system to meet the needs of fracture channeling sealing in water drive wells. SUMMARY

[0008] The present application aims to overcome the defects of the prior art and provide a high-strength double-network gel for fracture channeling sealing in water drive wells and a preparation method thereof.

[0009] To achieve the above-mentioned purpose, the present application adopts the following technical solutions:

[0010] In a first aspect, a high-strength double-network gel for fracture channeling sealing in water drive wells comprises the following components by mass fraction:

[0011] 0.5-2 parts of a low-molecular-weight emulsion polymer;

[0012] 0.1-0.3 parts of a medium-molecular-weight polymer;

[0013] 0.1-0.4 parts of a phenolic crosslinking agent;

[0014] 0.1-0.4 parts of an aldehyde crosslinking agent;

[0015] 0.1-0.3 parts of an oxygen scavenger;

[0016] 96.6-98.9 parts of water.

[0017] Preferably, the low-molecular-weight emulsion polymer is a main blocking agent, which is prepared by copolymerization of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid sodium.

[0018] Preferably, the low-molecular-weight emulsion polymer has a molecular weight of 0.5-1 million.

[0019] Preferably, the low-molecular-weight emulsion polymer includes at least two of acrylamide, an anionic salt-tolerant monomer, and a non-ionic temperature-resistant monomer in the polymer monomer.

[0020] Preferably, the medium-molecular-weight polymer includes polyacrylamide, partially hydrolyzed polyacrylamide, acrylamide-2-acrylamide-2-methylpropane sulfonic acid sodium copolymer, and acrylamide-N-ethyl pyrrolidone copolymer.

[0021] Preferably, the medium-molecular-weight polymer has a molecular weight of 60-80 million.

[0022] Preferably, the phenolic crosslinking agent includes one or more of phenol, p-benzenediol, m-benzenediol, and pyrogallol.

[0023] Preferably, the phenolic crosslinking agent includes phenol, p-benzenediol, o-benzenediol, m-benzenediol, and pyrogallol.

[0024] Preferably, the aldehyde crosslinking agent includes one or more of formaldehyde, hexamethylenetetramine, and p-xylylene.

[0025] Preferably, the aldehyde crosslinking agent includes one or more of formaldehyde, hexamethylenetetramine, and p-xylylene.

[0026] Preferably, the mass ratio of the phenolic crosslinking agent and the aldehyde crosslinking agent is 1:(1-2) for use in reaction with the polymer to form the gel.

[0027] Preferably, the oxygen scavenger is thiourea or sodium sulfite.

[0028] In a second aspect, a method for preparing a high-strength double-network gel for use in fracture channeling blocking in pressure drive wells includes the following steps:

[0029] The formula amount of water is weighed, and then the formula amount of the phenolic crosslinking agent, the aldehyde crosslinking agent, and the oxygen scavenger are added, mixed, and stirred until the powder is completely dissolved. Then, the formula amount of the medium molecular weight polymer powder is weighed and slowly added to the solution while stirring. The stirring is performed at a speed of 120 r / min for 1 hour. Finally, the formula amount of the low molecular weight emulsion polymer is added, and the stirring is performed for another 1 hour until the gel liquid is uniformly mixed, thereby obtaining the high-strength double-network gel for use in fracture channeling blocking in pressure drive wells.

[0030] In summary, due to the adoption of the above technical solutions, the present application has the following beneficial effects:

[0031] In the present application, a high-strength double-network gel is provided. Through the synergistic effect of the low molecular weight polymer and the medium and high molecular weight polymer, the double-network gel is constructed to improve the shear resistance and the plugging strength, so that the shear resistance, temperature resistance, salt resistance, and strength of the gel are greatly improved. The high-strength gel plug can be formed in the fracture in pressure drive, thereby effectively blocking water, expanding the water injection area in pressure drive, and improving the water injection efficiency. DETAILED DESCRIPTION

[0032] The following embodiments are further described to illustrate the specific implementation of the high-strength double-network gel for use in fracture channeling blocking in pressure drive wells and the method for preparing the same. The high-strength double-network gel for use in fracture channeling blocking in pressure drive wells and the method for preparing the same are not limited to the following descriptions of the embodiments.

[0033] Embodiment 1:

[0034] The high-strength double-network gel for use in fracture channeling blocking in pressure drive wells includes the following components in terms of mass fraction:

[0035] 0.5 parts of low molecular weight emulsion polymer;

[0036] 0.1 parts of medium molecular weight polymer;

[0037] 0.1 parts of phenolic crosslinking agent;

[0038] 0.1 part of aldehyde crosslinking agent;

[0039] 0.1 part of oxygen scavenger;

[0040] 96.6 parts of water.

[0041] Further, the low molecular weight emulsion polymer is the main agent of the plugging agent, which is copolymerized by acrylamide and 2-acrylamide-2-methylpropane sulfonic acid sodium.

[0042] Further, the low molecular weight emulsion polymer has a molecular weight of 500,000.

[0043] Further, the low molecular weight emulsion polymer includes acrylamide, an anionic salt-resistant monomer, and a non-ionic temperature-resistant monomer in the polymer monomer.

[0044] Further, the molecular weight polymer is polyacrylamide or partially hydrolyzed polyacrylamide.

[0045] Further, the molecular weight polymer has a molecular weight of 6,000,000.

[0046] Further, the phenolic crosslinking agent includes phenol, p-benzenediol, and o-benzenediol.

[0047] Further, the aldehyde crosslinking agent includes formaldehyde and hexamethylenetetramine.

[0048] Further, the mass ratio of the phenolic crosslinking agent and the aldehyde crosslinking agent is 1:1, which is used to react with the polymer to form a gel.

[0049] Further, the oxygen scavenger is thiourea.

[0050] Example 2:

[0051] A high-strength double-network gel for fracturing plugging in a pressure-driven well includes, by mass fraction, the following components:

[0052] 1 part of low molecular weight emulsion polymer;

[0053] 0.2 parts of medium molecular weight polymer;

[0054] 0.2 parts of phenolic crosslinking agent;

[0055] 0.2 parts of aldehyde crosslinking agent;

[0056] 0.2 parts of oxygen scavenger;

[0057] 97.7 parts of water.

[0058] Further, the low molecular weight emulsion polymer includes acrylamide, an anionic salt-resistant monomer, and a non-ionic temperature-resistant monomer in the polymer monomer.

[0059] Further, the low molecular weight emulsion polymer has a molecular weight of 1 million.

[0060] Further, the mass ratio of the phenolic crosslinking agent and the aldehyde crosslinking agent is 1:1.5, which is used to react with the polymer to form the gel.

[0061] Further, the oxygen scavenger is thiourea or sodium sulfite.

[0062] Further, the low molecular weight emulsion polymer has a molecular weight of 1 million.

[0063] Further, the molecular weight polymer has a molecular weight of 7 million.

[0064] Further, the phenolic crosslinking agent includes phenol, hydroquinone, catechol, resorcinol, and pyrogallol.

[0065] Further, the aldehyde crosslinking agent includes formaldehyde, terephthaldehyde, and hexamethylenetetramine.

[0066] Example 3:

[0067] A high-strength double-network gel for fracturing and channeling control in a pressure-driven well, comprising the following components by mass fraction:

[0068] 2 parts of a low molecular weight emulsion polymer;

[0069] 0.3 parts of a medium molecular weight polymer;

[0070] 0.4 parts of a phenolic crosslinking agent;

[0071] 0.4 parts of an aldehyde crosslinking agent;

[0072] 0.3 parts of an oxygen scavenger;

[0073] 98.9 parts of water.

[0074] Further, the low molecular weight emulsion polymer has a polymer monomer including acrylamide and an anionic salt-tolerant monomer.

[0075] Further, the molecular weight polymer is polyacrylamide or partially hydrolyzed polyacrylamide.

[0076] Further, the mass ratio of the phenolic crosslinking agent and the aldehyde crosslinking agent is 1:2, which is used to react with the polymer to form the gel.

[0077] Further, the oxygen scavenger is thiourea.

[0078] Further, the low molecular weight emulsion polymer has a molecular weight of 1 million.

[0079] Further, the molecular weight polymer has a molecular weight of 7 million.

[0080] Further, the phenolic crosslinking agent includes phenol, hydroquinone, resorcinol, pyrogallol.

[0081] Further, the aldehyde crosslinking agent includes formaldehyde, hexamethylenetetramine, p-xylylene.

[0082] Example 4:

[0083] A preparation method of a high-strength double-network gel for pressure-driven well fracture channeling sealing, comprising the following steps:

[0084] Firstly, the formation water (salinity 100000 mg / L) is weighed according to the predetermined formulation of the gel, then the phenolic crosslinking agent, the aldehyde crosslinking agent and the oxygen scavenger are added, and after mixing, the powder is stirred until completely dissolved, then the medium molecular weight polymer powder is weighed and slowly added to the solution while stirring, and the stirring is carried out at a speed of 120 r / min for 1 hour, finally the low molecular weight emulsion polymer is added, and the stirring is carried out for another 1 hour until the gel liquid is uniformly mixed, thereby obtaining the gel liquid of the gel of the present application.

[0085] Example 5:

[0086] The gel liquid is prepared according to 2% low molecular weight polymer, 0.3% medium molecular weight polymer, 0.4% phenolic crosslinking agent, 0.4% aldehyde crosslinking agent and 0.3% oxygen scavenger, then the bottle test experiment and the physical simulation experiment are carried out, and the gel time, strength, temperature resistance and salt resistance and channeling sealing capacity of the gel are evaluated.

[0087] Example 6:

[0088] The gel liquid is prepared according to 0.5% low molecular weight polymer, 0.3% medium molecular weight polymer, 0.4% phenolic crosslinking agent, 0.4% aldehyde crosslinking agent and 0.3% oxygen scavenger, then the bottle test experiment and the physical simulation experiment are carried out, and the gel time, strength, temperature resistance and salt resistance and channeling sealing capacity of the gel are evaluated.

[0089] Example 7:

[0090] The gel liquid is prepared according to 2% low molecular weight polymer, 0.1% medium molecular weight polymer, 0.4% phenolic crosslinking agent, 0.4% aldehyde crosslinking agent and 0.3% oxygen scavenger, then the bottle test experiment and the physical simulation experiment are carried out, and the gel time, strength, temperature resistance and salt resistance and channeling sealing capacity of the gel are evaluated.

[0091] Example 8:

[0092] The gel liquid is prepared according to 2% low molecular weight polymer, 0.3% medium molecular weight polymer, 0.1% phenolic crosslinking agent, 0.1% aldehyde crosslinking agent and 0.3% oxygen scavenger, then the bottle test experiment and the physical simulation experiment are carried out, and the gel time, strength, temperature resistance and salt resistance and channeling sealing capacity of the gel are evaluated.

[0093] Comparative Example 1:

[0094] The gelation liquid was prepared according to 2% low molecular weight polymer, 0.4% phenolic crosslinking agent, 0.4% aldehyde crosslinking agent, 0.3% oxygen scavenger, and then bottle test and physical simulation experiment were carried out to evaluate the gelation time, strength, temperature and salt resistance and channeling sealing capacity of the gel.

[0095] Comparative Example 2:

[0096] The gelation liquid was prepared according to 0.3% medium molecular weight polymer, 0.4% phenolic crosslinking agent, 0.4% aldehyde crosslinking agent, 0.3% oxygen scavenger, and then bottle test and physical simulation experiment were carried out to evaluate the gelation time, strength, temperature and salt resistance and channeling sealing capacity of the gel.

[0097] Comparative Example 3:

[0098] The gelation liquid was prepared according to 2% low molecular weight polymer, 0.3% medium molecular weight polymer, 0.4% phenolic crosslinking agent, 0.4% aldehyde crosslinking agent, 0.3% oxygen scavenger, and then bottle test and physical simulation experiment were carried out to evaluate the gelation time, strength, temperature and salt resistance and channeling sealing capacity of the gel. Different from Example 5, the gelation time, strength, temperature and salt resistance and channeling sealing capacity evaluation was carried out at 150°C.

[0099] Comparative Example 4:

[0100] The gelation liquid was prepared according to 2% low molecular weight polymer, 0.3% medium molecular weight polymer, 0.4% phenolic crosslinking agent, 0.4% aldehyde crosslinking agent, 0.3% oxygen scavenger, and then bottle test and physical simulation experiment were carried out to evaluate the gelation time, strength, temperature and salt resistance and channeling sealing capacity of the gel. Different from Example 5, the gelation liquid was prepared using formation water with salinity of 200000 mg / L.

[0101] Gel performance evaluation:

[0102] Gelation time and gel strength determination: After preparing the gelation liquid according to the requirements of the examples and comparative examples, it was divided into ampoule bottles and sealed, and then the ampoule bottles were sealed in an aging tank and aged at 130°C. The gelation time and strength of the gel were determined by visual observation method. After the gel was aged for 3 days, the gel sample was taken out and the storage modulus of the gel was measured at room temperature using a rheometer to quantitatively evaluate the gel strength.

[0103] Gel temperature and salt resistance evaluation: After preparing the gelation liquid according to the requirements of the examples and comparative examples, it was divided into ampoule bottles and sealed, and then the ampoule bottles were sealed in an aging tank and aged at a certain temperature for 90 days. The dehydration rate of the gel system was determined. The dehydration rate is defined as the ratio of the mass of water separated after the gel is aged to the initial mass of the gel.

[0104] Gel sealing and cross-contamination capability test:

[0105] The gel sealing and channeling ability was tested using a physical model experimental setup. The model consisted of a 25cm long gel with an inner diameter of 2.5cm and a matrix permeability of 0.5-1×10³μm. 2 Core samples with a fracture width of 1 mm were tested under simulated conditions of 130℃ and 100,000 mg / L formation water salinity. The experiment mainly evaluated the plugging capacity of the system. Therefore, 0.5 PV of plugging agent was injected into the core sample, sealed and aged for 2 days until the gel was completely gelled, and then the plugging rate was measured. The plugging rate was calculated from the equivalent permeability before and after plugging. The test results are shown in Table 1.

[0106] Table 1. Results of gel performance tests

[0107]

[0108] Note: P1 is a low molecular weight emulsion polymer, and P2 is a medium molecular weight polymer.

[0109] The test results show that the amount of both polymers significantly affects the gel performance. Decreasing the amount of either polymer increases the gelation time, decreases the gel strength, and reduces the sealing rate in the crack model. Conversely, decreasing the mass fraction of the crosslinking agent prolongs the gelation time, weakens the gel strength, and reduces the sealing rate.

[0110] As shown in Comparative Example 1, using only low-molecular-weight polymers instead of medium-molecular-weight polymers results in a significant decrease in the strength of the single-network gel, with the storage modulus failing to reach 50 Pa and the plugging strength also significantly reduced. Comparative Example 2, a conventional single-network gel, exhibits significant differences in gel strength, plugging rate, and temperature and salt resistance compared to the present invention. The dual-network gel of the present invention shows a more than 20-fold increase in gel strength. Comparative Examples 3 and 4 demonstrate that the dual-network gel exhibits significant performance changes under high-temperature and high-salt conditions. Increased temperature significantly shortens the gel formation time and slightly increases the gel strength; increased mineralization slightly prolongs the gel formation time and decreases the strength. While changes in temperature and mineralization have little impact on the short-term plugging strength of the gel, they significantly affect its stability. After 90 days of aging, the gel dehydration rate exceeds 37%, causing volume shrinkage and plugging failure.

[0111] By adopting the above technical solution:

[0112] The low molecular weight polymer has a short molecular backbone and weak network entanglement, and is not easy to be sheared and damaged in high-speed migration. The polymer solution has low viscosity, and can improve the polymer concentration while ensuring low solution viscosity and easy injection, thereby improving the gel stability. In addition, the polymer monomer contains anionic and non-ionic temperature-resistant and salt-resistant monomers, and the gel formed by crosslinking of the polymer has excellent temperature resistance and salt resistance.

[0113] The medium and high molecular weight polymer has a long molecular backbone, but the amount is small, and will not significantly increase the solution viscosity. When used in combination with the low molecular weight polymer, the migration is protected by the low molecular weight polymer, and the shear resistance is improved. Compared with the low molecular weight polymer, the polymer has more crosslinking sites, and can significantly improve the crosslinking strength of the polymer gel. The three-dimensional networks formed by different length polymer molecules interpenetrate to form a double network, and under the synergistic action of the double network, the strength of the formed gel can be further enhanced.

[0114] The present application has temperature resistance of 130 DEG C and salt resistance of 100000 mg / L, and can effectively plug water channeling in the fracture of the pressure drive well.

[0115] The gel has a gelation time of 3-10 h at 130 DEG C, and the storage modulus after gelation is higher than 50 Pa, which is much higher than that of general high-strength gel, and the channeling plugging strength is high, and the plugging rate is higher than 95%.

[0116] The above is a further detailed description of the present application in combination with specific preferred embodiments, and the specific implementation of the present application cannot be limited to these descriptions. For ordinary skilled persons in the technical field to which the present application belongs, some simple deductions or substitutions can be made without departing from the concept of the present application, and all of them should be regarded as falling within the protection scope of the present application.

Claims

1. A high-strength dual-network gel for frac-plug sealing of fractures in a well, characterized in that, By mass fraction, comprising the following components: 0.5-2 parts of low molecular weight emulsion polymer; 0.1-0.3 parts of medium molecular weight polymer; 0.1-0.4 parts of phenolic crosslinking agent; 0.1-0.4 parts of aldehyde crosslinking agent; 0.1-0.3 parts of oxygen scavenger; 96.6-98.9 parts of water.

2. A high strength dual network gel for frac and channel plugging in a pressure activated well according to claim 1, characterized in that: The low molecular weight emulsion polymer is the main agent of the plugging agent, which is copolymerized by acrylamide and 2-acrylamide-2-methylpropanesulfonic acid sodium.

3. A high strength dual network gel for frac and channel plugging in a pressure activated well according to claim 2, characterized in that: The low molecular weight emulsion polymer has a molecular weight of 0.5-1 million.

4. A high strength dual network gel for frac and channel plugging in a pressure-flooded well according to claim 1, characterized in that: The low molecular weight emulsion polymer includes at least two of acrylamide, anionic salt-resistant monomer, and non-ionic temperature-resistant monomer in the polymer monomer.

5. A high strength dual network gel for frac and channel plugging in a pressure-flooded well according to claim 1, wherein: The molecular weight polymer includes polyacrylamide, partially hydrolyzed polyacrylamide, acrylamide-2-acrylamide-2-methylpropanesulfonic acid sodium copolymer, and acrylamide-N-ethylpyrrolidone copolymer.

6. A high strength dual network gel for frac and channel plugging in a pressure-flooded well according to claim 5, characterized in that: The molecular weight polymer has a molecular weight of 60-80 million.

7. A high strength dual network gel for frac and channel plugging of a pressure-flooded well according to claim 1, characterized in that: The phenolic crosslinking agent includes one or more of phenol, p-benzenediol, m-benzenediol, and pyrogallol.

8. A high strength dual network gel for frac and channel plugging of a pressure-flooded well according to claim 7, characterized in that: The phenolic crosslinking agent includes phenol, p-benzenediol, o-benzenediol, m-benzenediol, and pyrogallol.

9. A high strength dual network gel for frac and channel plugging of a pressure-flooded well according to claim 1, characterized in that: The aldehyde crosslinking agent includes one or more of formaldehyde, hexamethylenetetramine, and p-xylidine.

10. A high strength dual network gel for frac and channel plugging in a pressure-flooded well according to claim 9, characterized in that: The aldehyde crosslinking agent includes formaldehyde, p-xylidine, and hexamethylenetetramine.

11. A high strength dual network gel for frac and channel plugging in a pressure-flooded well according to claim 1, characterized in that: The mass ratio of the phenolic crosslinking agent and the aldehyde crosslinking agent is 1:(1-2), which is used to react with the polymer to form a gel.

12. A high strength dual network gel for frac and channel plugging in a pressure activated well according to claim 1, wherein: The oxygen scavenger is thiourea and sodium sulfite.

13. A method of preparing a high-strength dual-network gel for frac-plug sealing of fractures in a well, the method comprising: combining a first network-forming material and a second network-forming material to form a mixture; and curing the mixture to form the high-strength dual-network gel. The method comprises the following steps: The formula amount of water is weighed, and then the formula amount of phenolic crosslinking agent, aldehyde crosslinking agent, and oxygen scavenger is added. After mixing, stirring is performed until the powder is completely dissolved. Then, the formula amount of medium molecular weight polymer powder is weighed and slowly added to the solution while stirring. Stirring is performed at a speed of 120 r / min for 1 hour. Finally, the formula amount of low molecular weight emulsion polymer is added, and stirring is performed for another 1 hour until the gel liquid is uniformly mixed, thereby obtaining a high-strength double-network gel for pressurized fracturing and channeling control.

Citation Information

Patent Citations

  • Slow-crosslinked high-strength jelly profile control water-plugging agent

    CN106479463A

  • High-temperature-resistant high-strength gel material and application thereof

    CN112724947A

  • High-strength gel temporary plugging agent for plugging horizontal shaft before well repair of thermal recovery horizontal well and preparation method thereof

    CN113025292A